Influences of fatigue stiffness degradation of in-service concrete T-beams on natural vibration frequency - Xin-Dai Zuo; Ying-Sheng Ni; Jin-Quan Zhang; Shang-Chuan Zhao (Journal of Asian Architecture and Building Engineering)
In order to obtain the fatigue stiffness degradation law of in-service concrete T-beam and carry out fatigue life prediction, a dual-stage stiffness degradation model considering cracks was established for T-beams and formulas for calculating the fundamental frequency of damaged concrete T-beams were deduced based on relevant theories of damage mechanics. The developed model aimed to investigate the influences of the fatigue stiffness degradation of in-service concrete T-beams on the natural vibration frequency of structures. A fatigue test was conducted for full-scale test beams to examine the crack development and fundamental frequency change law of structures during the fatigue process. Based on a full scale model of 10 m reinforced concrete T-beams, static and fatigue failure tests were carried out to obtain the evolution law of fatigue residual stiffness with load times. Fatigue damage coefficient D and stiffness degradation coefficient k were introduced to establish the fatigue life prediction model of T-beams in service. In line with the related test data and fundamental frequency formulas, stiffness updating methods were put forward for the concrete T-beam finite element models. By comparing the calculated value and test value of the natural vibration frequency of structures, the relative error was estimated to be within 6%. This verified the accuracy and reliability of the fundamental frequency calculation formulas and the updated finite element models. The research results can be used as a reference for the precise simulation of the fatigue damage finite element models of concrete T-beams. Finally, a method for life prediction of in-service reinforced concrete beam Bridges is proposed, and relevant research results can provide theoretical support for the study of life prediction of such Bridges.